Survey on Effective Disposal of E-Waste to Prevent Data Leakage - Victor, Akila; Arunkumar, Gurunathan; Kannadasan, Rajendran; Rajkumar, Soundrapandiyan; Selvanambi, Ramani (Computer Assisted Methods in Engineering and Science, 2024)
E-waste refers to electronic products that are of no use, not working properly, and either close to or at the end of their “useful life”. Companies generate large amounts of e-waste when they replace old and outdated IT hardware with new technologies. Disposing of this e-waste is not so simple, as it may contain a significant amount of intellectual property in the form of data. Timely elimination of these records and data is very crucial to secure it. E-waste cannot just be discarded due to associated data security, confidentiality, compliance and environmental risks and policies. Even after deleting data, it can still be prone to social engineering attacks by malicious individuals. Data leakage is the unauthorized transmission of data from within an organization to an external destination or recipient, and it can be transferred electronically or physically. Nowadays, protecting data is of upmost importance for organizations. However, organizations still fail at destroying confidential data from their end-of-life equipment. This article focuses on how to detect data leakage and try to find those responsible for doing so. Different Data Loss Prevention (DLP) techniques that are currently being used by many organizations are discussed and some suggestions are provided for developing more consistent DLP and overcoming the weaknesses prevalent in these techniques. Furthermore, this article discusses various algorithmic, logical, and methodological foundations and procedures followed for large-scale data disposal, determining when the life of data comes to an end.